Using a Trade Market Analysis Technique to Refine Measurements for Economic Impact Analysis of Special Events. (January 2015) - Warnick, Rodney B.; Bojanic, David C.; Xu, Feng
Special events can have a sizable economic significance (ES) and economic impact (EI) in host communities. This study's purpose was to update the input measurement concepts in assessing the EI for a short-term special event. Specific EI measurements were examined as suggested by Crompton, Lee, and Shuster (2001) and Stynes (1997) that differentiated between types of attendees. A trade market analysis (TMA) technique was applied to refine the measures of locals and nonlocals and to reconsider locals who have visiting friends and relatives (VFR) in their group profiles. Further refinement of day-trip attendees and visitors expenditure impacts were identified and used to adjust the EI when applied to a sales multiplier. Self-administered online surveys were emailed to 2, 678 group leaders from a registration and on-site intercept population with a response rate of 46%. Measurement improvements were found for local, nonlocal, casual, time-switcher, and VFR attendees in EI application.